Antibacterial Activity Of Chromolaena odorata (L) King Leaves With Bioautography - Siti Rofida; Nurwahdaniati Nurwahdaniati (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2015)
ABSTRACT Chromolaena odorata (L) King, commonly referred as kirinyuh, is a traditional medicinal plant from Asteraceae. It has been reported that C. odorata scientifically possessed antimicrobial activity. The aim of this study is to obtain active antibacterial substances from 70% etanolic extract of C. odorata against Staphylococcus aureus. Separation of active substances was carried out by Thin Layer Chromatography (TLC) techniques. The separated substances were tested for their antibacterial activity by bioautography assay using S. aureus. Separation of 70% etanolic extract C. odorata produced six spots with retention factor (Rf) values are 0.9, 0.8, 0.7, 0.6, 0.5, and 0.3. The diameters of inhibition zone of those spots were 35, 27, 27, 20, 31, and 14 mm, respectively. Based on the TLC profiles, the compounds with Rf of 0.9, 0.6, and 0.5 were identified as flavonoids and the compounds with Rf of 0.8, 0.7, and 0.3 were identified as terpenoids. It is concluded that the spot with the most potent antimicrobial activity was flavonoids with of Rf 0.9. Key words: antibacterial, bioautography, Chromolaena odorata.